Poranění mediálních struktur u zlomenin hlezna – epidemiologické aspekty a hodnocení výsledků léčby - Ježek, J; Skála-Rosenbaum, J; Čech, P; Svatoš, F; Vránová, J; Marvan, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY Ankle fractures are characterised by a high variability of damage to bone and ligament structures which leads to diverse clinical conditions. This study aims to analyse a group of patients with surgically treated ankle fractures, with a focus on evaluating the outcomes of treatment of ankle joint medial structure injuries (medial malleolar fracture, ligament lesions). MATERIAL AND METHODS The analysed group included 186 patients (102 men and 84 women), in whom an ankle fracture surgery was performed in 2015 and 2016. The outcomes of the treatment were evaluated in 111 patients with type B and type C fractures, who underwent a follow-up examination at one year after the surgery consisting in subjective and objective assessment of the condition and an ankle radiograph. The obtained outcomes were processed using the techniques of descriptive statistics and subsequently evaluated through the Pearson´s chi-square test at 5% significance level, or the Fisher´s exact test for low frequencies. RESULTS The mean age of patients in the group was 48.6 years, while it was lower in men than in women (42.8 years compared to 53.9 years). According to Weber classification, 1 % of fractures were classified as a type A fracture, 68 % as a type B, 27 % as a type C. The group of isolated medial malleolar fractures represented 4 % of cases. The medial side of the ankle joint more frequently suffered a ligament lesion (56 %) than a medial malleolar fracture (44 %). The mean age of the patients with a medial malleolar fracture was 51.9 years, whereas the mean age of the patients with a ligament lesion on the medial side of the ankle was 44.2 years. When evaluating the outcomes using the OMA score at one year postoperatively, a statistically significant difference was found (p = 0.002) between the patients with a medial malleolar fracture (OMA 79.9) and the patients with a ligament lesion at the medial side of the ankle joint (OMA 91.2). DISCUSSION The aim of the study was to add more information on medial structures of ankle joint that are of major importance for ensuring stability of ankle fractures. In agreement with the literature, when managing the ankle fractures with an injury suffered on the medial side there is obviously a more uniform approach in cases with medial malleolar fractures. The situation is different in case of the deltoid ligament lesion, when historically there is a certain level of non-uniformity in indications for revision surgeries and treatment of the injured ligament structures. In our group, in the case of ligament lesion on the medial side of the ankle joint an emphasis is put on the fluoroscopy control of the symmetry of tibiotalar joint space before the beginning of the surgery and also after the fibular fracture stabilisation. The revision surgery was indicated in cases where asymmetry of ankle fork was found. The patients considered the treatment outcome better in cases with a ligament lesion than in cases with a medial malleolar fracture. CONCLUSIONS Proper treatment of medial structures of the ankle joint is important for ensuring the stability of ankle fractures. The patients with type B fractures reported better results at one year postoperatively compared to the patients with type C fracture according to the Weber classification. A statistically significantly better results after the ankle fracture surgery were achieved in patients with the presence of a medial ligament lesion compared to the patients with a medial malleolar fracture. Key words:ankle fracture, injury of medial structures, epidemiology, outcomes of treatment.
Keywords: výsledek terapie; Ankle Injuries; Middle Aged; mužské pohlaví; ženské pohlaví; poranění kotníku; Fracture Fixation, Internal; dospělí; Humans; Treatment Outcome; Adult; Female; Ankle Fractures; vnitřní fixace fraktury; fraktury kotníku; lidé; Male; lidé středního věku